Globalisation, NGOs and Multi-Sectoral Relations: The Zimbabwean Experience 1980–2012 - Tarugarira, Gilbert (Routledge, 2021)
Africa has encountered the diffusion of Western capitalism and cultural values and a network of socioeconomic and political institutions which have made her political economy the most vulnerable to both positive and negative external influences. The theme of Africa’s massive marginalisation under globalisation resonates with Mazrui (2005, p. 62) who argues that whilst ‘the continent helped to develop Europe through labour, territory and extractive imperatives of the colonial era, every stage of Africa’s contribution to globalisation was also a stage in its own marginalisation’. The last years of colonial rule and the first years of independence in Africa which Mazrui (1977, p. 33) has termed the ‘golden age of liberalism’ saw the idea of majority rule, electoral freedom, a free press, competitive parties and open debate finding genuine realisation. Upon gaining flag independence, the African leaders found themselves entangled in a world order and global system dominated by the highly industrialised powerful nations that jealously protected their markets and industries. The Organisation of African Unity (now the African Union) was created to address local African problems and to prevent foreign intervention and external manipulation, which globalisation so freely allows.